Aesthetic preference in the production of image sequences - Monroy, Ernesto; Orgs, Guido; Sagiv, Noam (Frontiers in Psychology, 2023)
Introduction This research uses the production method to study aesthetic preference for sequences of human body postures. In two experiments, participants produced image sequences based on their aesthetic preferences, while we measured the visual aesthetic features displayed in the compositions. Methods In Experiment 1, participants created static image sequences based on their preferences. In Experiment 2, participants sorted images into apparent motion sequences they preferred to view. Results In Experiment 1, good continuation of successive bodies and body-like objects was the preferred order. In Experiment 2, participants preferred abstract images with local sequential symmetry and human body postures exhibiting global sequential symmetry. Discussion Our findings are compared to those of previous studies that employed the more widely used method of choice. Our experiments propose novel methods and conceptualizations for investigating aesthetic preferences for human body movement and other types of stimulus sequences.